2011
DOI: 10.1155/2011/516739
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Near-IR S0 Galaxy Survey (NIRS0S)

Abstract: An overview of the results of the Near-IR S0 galaxy Survey (NIRS0S) is presented. NIRS0S is a magnitude (m B 12.5 mag) and inclination (< 65 o ) limited sample of ∼ 200 nearby galaxies, mainly S0s, but include also Sa and E galaxies. It uses deep K s -band images, typically reaching a surface brightness of 23.5 mag arcsec −2 . Detailed visual and photometric classifications were made, for the first time coding also the lenses in a systematic manner. The main analysis methods include 2D multicomponent decomposi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 79 publications
4
15
0
Order By: Relevance
“…Fast rotators have similar intrinsic flattening as spiral galaxies, which is in line with the results of Paper XVII, where we showed that fast rotators show a large span in disc-to-total ratios, and with the classification scheme introduced by Van den Bergh (1976), and revisited in Paper VII to emphasize the parallelism between fast rotators and spirals (see also Laurikainen et al 2011;Kormendy & Bender 2012). This observation could hint to a similar evolutionary path of spirals and fast rotators, and it would be interesting to study this further in the context of the morphologydensity relation, as mentioned in e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Fast rotators have similar intrinsic flattening as spiral galaxies, which is in line with the results of Paper XVII, where we showed that fast rotators show a large span in disc-to-total ratios, and with the classification scheme introduced by Van den Bergh (1976), and revisited in Paper VII to emphasize the parallelism between fast rotators and spirals (see also Laurikainen et al 2011;Kormendy & Bender 2012). This observation could hint to a similar evolutionary path of spirals and fast rotators, and it would be interesting to study this further in the context of the morphologydensity relation, as mentioned in e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Graham 2001;MacArthur et al 2003;Weinzirl et al 2009;Laurikainen et al 2010), and strongly suggest an evolutionary link. Our results support the revision of the Hubble diagram put forward initially by van den Bergh (1976), which we revised to include fast and slow rotators in Paper VII (for photometric investigations see Laurikainen et al (2011) and Kormendy & Bender (2012)).…”
Section: Similarities Of Fast Rotators Galaxies and Spiralssupporting
confidence: 87%
“…We showed that the true parallelism is the one between fast rotator ETGs and spirals instead (Cappellari et al 2011b, hereafter Paper VII). Similar conclusions were also reached using photometry by Laurikainen et al (2011) and Kormendy & Bender (2012).…”
Section: Introductionsupporting
confidence: 79%